2016
DOI: 10.1021/acschembio.5b00800
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Large-scale Behavioral Profiling in Zebrafish to Explore Neuroactive Polypharmacology

Abstract: Many psychiatric drugs modulate the nervous system through multi-target mechanisms. However, systematic identification of multi-target compounds has been difficult using traditional in vitro screening assays. New approaches to phenotypic profiling in zebrafish can help researchers identify novel compounds with complex polypharmacology. For example, large-scale behavior-based chemical screens can rapidly identify large numbers of structurally diverse and phenotype-related compounds. Once these compounds have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…For instance, software that can discriminate between the tail, mid‐body and nose of the zebrafish are well capable of quantifying locomotion and interpreting complex behaviours such as chasing or nipping, chasing (Kalueff et al ., ; Stewart et al ., ). These methods are especially useful in polypharmacology studies using pharmacological agents that act on multiple targets (McCarroll et al ., ). As many psychiatric disorders are linked to deficits in several neurotransmitter systems and have multigenic aetiologies (Kendler et al ., ; Schizophrenia Working Group of the Psychiatric Genomics Consortium, ), this possibility in zebrafish screens becomes particularly important.…”
Section: Perspectives On Small Molecule and Genetic Screening In Zebrmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, software that can discriminate between the tail, mid‐body and nose of the zebrafish are well capable of quantifying locomotion and interpreting complex behaviours such as chasing or nipping, chasing (Kalueff et al ., ; Stewart et al ., ). These methods are especially useful in polypharmacology studies using pharmacological agents that act on multiple targets (McCarroll et al ., ). As many psychiatric disorders are linked to deficits in several neurotransmitter systems and have multigenic aetiologies (Kendler et al ., ; Schizophrenia Working Group of the Psychiatric Genomics Consortium, ), this possibility in zebrafish screens becomes particularly important.…”
Section: Perspectives On Small Molecule and Genetic Screening In Zebrmentioning
confidence: 97%
“…The combination of behavioural phenotyping and computation techniques is useful in the development and discovery of new medical targets, including in vivo behavioural phenotyping of single target compounds in 2D or 3D tracking, producing their unique swim traces (thigmotaxis, scototaxis, average swim speed, etc. ), identifying the compounds that produce the desired behavioural phenotype (hit compounds) and their subsequent in‐depth analyses with algorithms that predict their biological target(s) to generate hypotheses of target combinations (McCarroll et al ., ). Once identified, multiple hit compounds can then be tested in combination in vivo (McCarroll et al ., ), probing their ability to work in concert to achieve a desired therapeutic outcome.…”
Section: Perspectives On Small Molecule and Genetic Screening In Zebrmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this may also increase the side effect potential and the potential of interacting with other therapeutics. It has been suggested that large-scale zebrafish behavioral testing models can be used to help discern the polypharmacological mechanisms of neuroactive compounds [126]. This provides an ideal platform with which to test cannabis derivatives.…”
Section: Multi-drug Interactions and Polypharmacologymentioning
confidence: 99%
“… 27 Another facet is the application of high-capacity screening in very small animals, such as zebrafish and C. elegans . 7 , 28 30 Phenotypic screening methods can also be used to identify new drug targets and new indications for existing drugs. 7 , 31 The pinpointing of new molecular targets from phenotypic assays has greatly benefited from progress in chemical proteomics.…”
Section: Re-emergence Of Phenotypic Assessmentmentioning
confidence: 99%